Efektivitas Latihan Menggunakan Penghalang Gawang Terhadap Ketepatan Shooting Petanque - Dermawan, Giaz Fathoni; Nurhidayat, Nurhidayat (Jurnal Porkes, 2022)
This research was motivated by the not yet maximal shooting game ability possessed by UMS petanque athletes, considering that there was no preparation of training models to further develop shooting abilities. The purpose of this research is to find out Effects of Implementing Shooting Practice Using Barriers on Shooting Game Ability in UMS Petanque Athletes. The purpose of training using a barrier is to get athletes accustomed to throwing boules to boules. The method used is an experiment using a "one group pre test post test design" design. This study used shooting game station 1, 2, 3, 4, 5 instruments and throwing distances of 8 m. The subjects in this study were 15 UMS petanque athletes. The sample was selected using purposive sampling technique.Based on the results of the calculation of the hypothesis test, it can be seen that the shooting practice using a barrier has a significance value of 0.000 0.05 so that it can be said that there is a significant effect of shooting practice using a barrier on the improvement of shooting game results in UMS petanque athletes. Can be concluded that shooting practice model using a barrier can significantly improve shooting results in UMS petanque athletes. Ifseen from the mean value (mean) of the pretest of 3,40 and the mean value of (mean) of the posttest of 7,60 This shows that the exercise carried out can provide an increase of 4.20